An Investigation into the Perspectives and Experiences of Physically Active Adults During the COVID-19 Pandemic - Andy Pringle; Evelyn Oldale; Ella Rowley; Clare M. P. Roscoe (Behavioral Sciences)
Contemporary physical activity (PA) strategies emphasise the PA needs of sedentary and inactive groups, with less emphasis placed on physically active groups. Understanding the needs of physically active groups is important in helping people to keep active. This study investigated the perspectives and experiences of physically active adults (‘Actives’) during the COVID-19 pandemic, including their PA levels, barriers and facilitators to/for PA, the strategies they deployed to keep active and their experiences of the messaging of Government health and PA guidelines. Following recruitment, thirteen in depth semi-structured interviews were undertaken with adult men and women who reported meeting the UK Chief Medical Officer’s PA guidelines before the COVID-19 pandemic commenced. Braun and Clarke’s thematic analysis identified five key themes and related sub-themes: (I) PA participation; (II) barriers to PA participation, including overcrowding of the PA space, conflict between different groups and negative mental health; (III) facilitators for PA, including place/residence, rural location, social support and good mental wellbeing; (IV) strategies to keep active, including improvisation, substitution of PA mode, scheduling PA, social support and goal setting; (V) guidance and messaging on the health guidelines, including PA promotion for strength and balance, mental health and where to receive information on PA. This study provides valuable insights for PA promotion for Actives at an unprecedented time.